Simulation of Fracturing Process for Heterogeneous Material Using FLAC3D - Su, G.S.; Jiang, J.Q.; Zhou, H.F. (Asian Journal of Chemistry, 2014)
A novel numerical model for simulating the fracturing process of heterogeneous materials has been developed and implemented into the FLAC3D. A constitutive model that captures an essential component of brittle material failure i.e., cohesion weakening and frictional strengthening is improved by taking into account that the elastic modulus of an element may degrade when the element fails. Furthermore, a new energy index, the local energy release rate (LERR), is proposed that simulates the energy released during a failure process through tracking the peak and trough values of the elastic strain energy intensity. The numerical model has been applied to simulate the fracturing processes of a heterogeneous material, such as rocks, under a traixial loading condition are simulated by the proposed numerical model. The results demonstrate that the proposed model is a powerful approach for studying the macroscopic fracturing process of a heterogeneous material.